Legal Certainty Regarding Execution Practicesnon-Fungible Tokenas An Object of Fiduciary Guarantee - Andalusia (Ekasakti Journal of Law and Justice, 2026)
The development of blockchain technology has given birth to new digital assets, namely Non-Fungible Token (NFT). Its popularity has grown rapidly, transforming it from a mere digital collectible into a high-value investment instrument. This phenomenon opens up opportunities for NFTs to be utilized in various financial sectors, including as collateral. Its significant economic potential drives the need to examine its legal position within the existing financial system. Despite its economic value, the legal status of NFTs as fiduciary collateral in Indonesia remains unclear. The current Law Number 42 of 1999 concerning Fiduciary Collateral is designed for conventionally recognized tangible and intangible movable objects. The absence of specific regulations governing digital assets such as NFTs creates a legal vacuum, creating uncertainty for parties seeking to utilize them. This research is a legal research (doctrinal research) with a legal approach (statues approach), conceptual approach (conceptual approach), and analytical approach (analytical approach). The results of this study explain that first, the existence of Non-Fungible Token The development of NFTs as digital assets in Indonesia began with the development of the digital economy and increased public interest in using investment instruments. Second, the lack of specific regulations for NFTs as fiduciary collateral creates a significant legal vacuum, and the current Fiduciary Guarantee Law is not designed to accommodate the unique characteristics of digital assets, such as value volatility and technical identification. Third, accurately identifying NFTs during the execution process is a fundamental challenge. Unlike physical assets, NFTs can only be recognized through a series of cryptographic data such as token IDs and complex contract addresses. Current regulations fail to accommodate their unique characteristics related to classification, valuation, and registration and execution mechanisms. This situation creates significant legal uncertainty, thus creating high risks for the parties involved. The recommendation for this issue is the need for the government to immediately revise fiduciary guarantee regulations or establish specific regulations for digital assets. In the meantime, the government can create regulations in the form of Government Regulation in Lieu of Law (Perppu) or Supreme Court Rules (Perma) so that the legitimacy of digital asset objects such as NFTs is legally recognized as a class of movable and intangible assets in fiduciary guarantees.